2022
DOI: 10.3390/molecules27217364
|View full text |Cite
|
Sign up to set email alerts
|

Levetiracetam Ameliorates Doxorubicin-Induced Chemobrain by Enhancing Cholinergic Transmission and Reducing Neuroinflammation Using an Experimental Rat Model and Molecular Docking Study

Abstract: Cancer chemotherapy-induced cognitive impairment (chemobrain) is a major complication that affects the prognosis of therapy. Our study evaluates the nootropic-like activity of levetiracetam (LEVE) against doxorubicin (DOX)-induced memory defects using in vivo and molecular modelling. Rats were treated with LEVE (100 and 200 mg/kg, 30 days) and chemobrain was induced by four doses of DOX (2 mg/kg, i.p.). Spatial memory parameters were evaluated using an elevated plus maze (EPM) and Y-maze. Additionally, acetylc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 44 publications
1
23
0
Order By: Relevance
“…In order to identify molecular-level interactions, binding mode analysis was performed for those compounds that displayed binding affinity of −7 or above for AChE and −6 or above for COX-2; those binding modes were selected for discussion, which displayed interaction with key residues. The AChE literature search and crystal structure analysis revealed Tyr70, Asp72, Trp84, Gly118, Gly119, Tyr121, Ser200, Ala201, Trp279, Glu337, and His440 [ 27 , 28 , 29 ]. Similarly, for COX-2, the literature search and crystal structure analysis revealed Arg120, Ser530, Tyr355, Tyr385, Ala527, Val349, Leu352, Leu531, and Trp387 [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to identify molecular-level interactions, binding mode analysis was performed for those compounds that displayed binding affinity of −7 or above for AChE and −6 or above for COX-2; those binding modes were selected for discussion, which displayed interaction with key residues. The AChE literature search and crystal structure analysis revealed Tyr70, Asp72, Trp84, Gly118, Gly119, Tyr121, Ser200, Ala201, Trp279, Glu337, and His440 [ 27 , 28 , 29 ]. Similarly, for COX-2, the literature search and crystal structure analysis revealed Arg120, Ser530, Tyr355, Tyr385, Ala527, Val349, Leu352, Leu531, and Trp387 [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…For COX-2, Arg120, Ser530, Tyr355, Tyr385, Ala527, Val349, Leu352, Leu531 and Trp387 were considered important for binding mode analysis. In the case of AChE residues, Ser200, Glu337, and His440 form the catalytic triad, while residues Gly118, Gly119, and Alanine together make the oxyanion binding sites [ 27 , 28 ]. The peripheral aromatic binding site is made up of Asp72.…”
Section: Discussionmentioning
confidence: 99%
“…The rats were allocated to four groups (n = 6) for the experimental procedure. The schedules of the prophylactic drug (LEVE) treatment and induction of neurotoxicity (LPS) were followed according to previous reports with minor modifications ( Kamdi et al, 2021 , Mani et al, 2022a ). The control rats were administered 30 days with the vehicle (NS; 10 mL/kg, p.o.)…”
Section: Methodsmentioning
confidence: 99%
“…), and neuronal deficits were induced with LPS, similar to the LPS-induced group. The doses of LPS ( Rahim et al, 2021 ) and LEVE ( Mani et al, 2022a ) used in this experiment are based on our previous reports. For the assessment of cognitive performance, EPM procedures were carried out on days 26 (training) and 27 (retention).…”
Section: Methodsmentioning
confidence: 99%
“…A complex combination of genetic factors, life events, and lifestyles triggers these pathological processes. Mental triggers include traumatic events, depression ( Gu et al, 2022 ), physical stressors such as radiotherapy ( Gu et al, 2022 ; Gutierrez-Quintana et al, 2022 ), traumatic brain injury, viral or bacterial infections ( Akinci et al, 2022 ; Francis et al, 2023 ), and exposure to toxins such as toxic heavy metals ( Mani et al, 2022 ; Xu et al, 2022 ), insecticides, chemotherapy agents, medicaments, and a fatty diet. A recent study showed that neuroinflammation could also be associated with epigenetic changes induced by Posttraumatic Stress Disorder (PTSD) ( Wolf et al, 2018 ) (see Figure 1 ).…”
Section: Memory Loss During Agingmentioning
confidence: 99%